DAMPAK KECANDUAN MEDIA SOSIAL TIKTOK TERHADAP DISIPLIN BELAJAR PADA MAHASISWA ANGKATAN 2025 PRODI PPKn FKIP UNIVERSITAS JAMBI - Yunita Anggraini; Siti Tiara Maulia; Khusnul Khotimah (STKIP Subang, 2026)
This research was motivated by the high intensity of TikTok social media use among 2025 cohort students of the Civics Education Study Program (Prodi PPKn), FKIP, Universitas Jambi. Field phenomena revealed that excessive TikTok usage led to students delaying academic tasks, losing learning focus, managing time poorly, and covertly accessing the application during lectures. These issues indicated a decline in students' learning discipline in fulfilling their academic obligations. Based on these problems, this study aimed to analyze the implications of TikTok social media addiction on the learning discipline of these students based on their subjective experiences, as well as to identify the influencing factors within a social context. The research method employed a qualitative approach with a descriptive qualitative type. The research subjects involved the 2025 cohort students as primary informants, Civics Education lecturers as key informants, and 2024 cohort students as additional informants. Data were collected through observation, in-depth interviews, and documentation techniques, which were subsequently analyzed using the Miles and Huberman interactive model. The results showed that TikTok addiction had negative implications for students' learning discipline, characterized by decreased study focus, procrastination, lack of learning regularity, and disrupted academic time management. Factors influencing TikTok addiction among these students included high duration of use, the influence of social environments and peer groups, boredom, the need for entertainment, and weak self-control in prioritizing academic activities.